Effects of post-exercise honey drink ingestion on blood glucose and subsequent running performance in the heat - Ahmad, N. S.; Ooi, F. G.; Ismail, M. S.; Mohamed, M. (Asian Journal of Sports Medicine, 2015)
Background: Glycogen depletion and hypoglycemia have been associated with fatigue and decrement of performance during prolonged exercise.